Behavioral regulation in sport questionnaire and sport motivation scale-II: a scale comparison - Bica, Joana; Jacinto, Miguel; Matos, Rui; Amaro, Nuno; Antunes, Raúl; Couto, Nuno; Cid, Luís; Forte, Pedro; Monteiro, Diogo (Frontiers in Psychology, 2025)
IntroductionThis study compared the psychometric properties of two primary instruments for assessing sport motivation based on Self-Determination Theory: the Sport Motivation Scale-II (SMS-II) and the Behavioral Regulation in Sport Questionnaire (BRSQ).MethodsA cross-sectional analysis evaluated the scales’ internal consistency, factor structure, convergent and discriminant validity, and model fit, which required post-hoc modifications. Measurement invariance and adherence to the theoretical simplex pattern were also tested.ResultsThe BRSQ demonstrated generally acceptable reliability, while the SMS-II showed deficiencies in its introjected, external, and amotivation subscales. Both scales faced validity challenges in distinguishing adjacent motivational constructs. Although measurement invariance was supported, correlations deviated from the theoretical quasi-simplex pattern.DiscussionThe BRSQ appears more robust, but neither scale is flawless. Researchers must select instruments aligned with their specific objectives and interpret scores cautiously due to these psychometric limitations. This underscores the need for refined tools to better capture the dynamic complexity of motivation in sports.